Perceived Impact of Peer Influence on Cohabitation among Youth in Selected Off-Campus Areas in Ilorin Metropolis - Abdulhameed, Abdussalam; Abonyi, Sunday E.; Arinde-Simeon, Titilayo O. (ABUAD Journal of Social and Management Sciences, 2024)
The trend of cohabitation in our contemporary society, especially among the emerging youth, has increased moral decadence, which has caused more danger to the affected youth and culture. The study examined the perceived impact of peer influence on cohabitation among youth in selected off-campus areas in the Ilorin Metropolis. The study employed a survey method, and a sample size of 525 was randomly selected using purposive sampling for selection of the off-campus areas and simple random for the research participants, but only 497 participants filled out and returned the questionnaires. A Peer Influence Scale (PPS) for peer influence (x=0.87), a Self-developed Scale for gender, age and religion on cohabitation (x=0.85). Hypotheses were tested at a 0.05 significance level using a T-test and Analysis of Variance (ANOVA), while frequency counts and percentages were used to analyse the demographic data. The study found no significant difference in the influence of peers on cohabitation among youth in the Ilorin Metropolis based on gender. There was a significant difference in peer influence on cohabitation among youth in Ilorin Metropolis based on age. There was a significant difference in peer influence on cohabitation among youth in Ilorin Metropolis based on religion. Based on the study's findings, it recommended that concerted efforts should be made by the Social Workers, Social Welfare and other relevant stakeholders to engage in a sensitization programme that will re-orientate the teeming youth on the danger cohabitation can pose to their future well-being and welfare.